Impact of Dynamic Modeling of Urban Transportation in the evaluation of environmental pollution of the District of Pampas – Tayacaja (Alpha Centauri, 2023)
The growth of the population in cities leads to the generation of a series of activities that have a strong impact on the environment. One of them is activities related to urban transportation, negatively impacting the environment; as a result of motor vehicles in Peru that consume high gallons of fuel producing carbon dioxide CO2, Its accumulation in the atmosphere generates global warming and climate change. Another negative impact of urban transportation is sound pollution, due to the generation of noise during the activity. With the objective of understanding and proposing policies to change the problem of environmental pollution, The dynamic model has been built based on the system dynamics modeling process, a method of applying systemic thinking to understand and model the problem under study. It is concluded that policies to improve the use of alternative transportation such as bicycles, scooters and electric vehicles; They are forms of transportation that improve people's quality of life and, in turn, stabilize climate change in cities. reducing the massive emission of greenhouse gases, as well as the noise pollution caused by the vehicle fleet, reducing people's stress level.